Primary Biliary Cholangitis with Ankylosing Spondylitis - Young Mi Hong; Ki Tae Yoon; Mong Cho (The Korean Journal of Gastroenterology, 2022)
Primary biliary cholangitis is a chronic inflammatory autoimmune liver disease that is characterized by a positive antimitochondrial antibodies test and progressive destruction of the small intrahepatic bile duct. Ankylosing spondylitis is a chronic, systemic, inflammatory disease of the spine and the sacroiliac joints. The association between these two is very low. This paper reports a rare case who had ankylosing spondylitis and developed primary biliary cholangitis.